(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: Despite high vaccination coverage, whooping cough remains an important cause of childhood morbidity and mortality worldwide. Many countries are experiencing whooping cough epidemics, with vaccinated people accounting for a significant proportion of those affected.